PENGEMBANGAN BADAN USAHA MILIK DESA (BUMDES) DENGAN PENDEKATAN SUSTAINABLE LIVELIHOOD APPROACH (SLA) DI DESA GRENDEN KECAMATAN PUGER KABUPATEN JEMBER - Nurazizah, Marinda Ayu; Prianto, Fajar Wahyu; Lestari, Endah Kurnia; Wiryaningtyas, Dwi Perwitasari (Growth, 2024)
In the era of globalization and global competition, villages need to optimize their economic and social potential to achieve stability and sustainable growth. One way to achieve this goal is through the formation and development of Village-Owned Enterprises (BUMDes). This research aims to determine the utilization of assets and vulnerabilities faced by BUMDes Gunung Mulia and to determine the strategy for sustainable development of BUMDes Gunung Mulia. The research was conducted using a qualitative approach. In carrying out this research, the data collection techniques used were observation, interviews, documentation, literature study and questionnaires. The respondents were selected deliberately (purposive sampling), namely the research stakeholders related to BUMDes Gunung Mulia. Data analysis to answer this research uses the Sustainable Livelihood Approach (SLA) and SWOT analysis. The research results show that: 1) The use of the Gunung Mulia BUMDes asset focuses on optimizing social capital and establishing collaboration with partners such as SAMSAT, Bank Jatim and Bank BNI. Agro-tourism (mango, sapodilla and water apple plantations) also makes a significant contribution to village livelihoods; 2) In responding to these findings, several strategies that can be formulated include: (a) exploiting village potential by forming new business fields, (b) holding training to make human resources more qualified and (c) having competitiveness and turning trading businesses into distributors. To improve the performance of BUMDes Gunung Mulia, it is recommended to focus on two main aspects, namely utilization and handling vulnerabilities.